Transforming the Education System Amidst Technological Developments by Utilizing E-Learning in the Digital Era - Septa Syaidin Aksa (Konsultan Jurnal Ilmiah Indonesia, 2025)
E-learning has become a major innovation in education, offering flexible, interactive, and efficient solutions to traditional learning challenges. This study explores the development of e-learning technology, from its early computer-based applications to modern web-based applications utilizing Learning Management Systems (LMS). Furthermore, the study discusses the implementation of e-learning at various levels of education, from schools to universities, and identifies factors influencing its success, such as technological infrastructure readiness, educator competency, and students' digital literacy skills. The study's findings indicate that e-learning can expand access to learning resources, increase student engagement through interactive technology, and provide flexibility in time and place. However, key challenges include the technological gap between urban and rural areas, resistance to changes in teaching methods, and the need for specialized training for educators. With the support of inclusive education policies and sustainable infrastructure development, e-learning has the potential to transform the education system to become more modern, adaptive, and individual-oriented. This research is expected to provide insights for the development of more effective e-learning in the future.